(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article provides information about the geological and mineralogical condition of the mine during open pit mining. Its structural properties, chemical and physical properties are of great importance in the extraction of ores and minerals in mining enterprises. It is advisable to take into account the structure of the rock together with the mechanical properties of the rock when drawing up the scheme of mining processes. The size of the mine is important in determining the schedule of production of materials and the order of their extraction in open mining processes of mining enterprises. The purpose of this paper is to develop, validate and present a multi-stage methodology for three main interrelated components of open pit mine planning: design of controllable optimal stages, characterization of selective mining units and long-term production management of such processes. Mining optimization of planning. A hybrid solution methodology for open pit design using integer programming and local search heuristics is presented. Next, a hierarchical clustering approach with size and shape control combines blocks within the limited surface area dimensions of open pits, and thrust limits are presented, and finally, a full linear programming mathematical model of the mixed-methods mining system is introduced. uses produced capacities and aggregates as planning units to provide optimal mine utilization schedules. The open pit mining process planning tool enables the mine planner to optimize large-scale real-time multi-pit multi-process planning problems, taking into account mine fleet capacity, production capacity and method mix requirements.